Recent Updates in US-Central Asia Relations: The Consequences of the US Withdrawal from Afghanistan and the Need for a New Strategy - Shokhrukh Yunusov (International Journal of Education, Vocational and Social Science, 2023)
This article discusses the current condition of relations between the United States and Central Asia. As a historically advantageous geostrategic region, Central Asia has long attracted major powers. The United States has its own reasons for being keen on this strategic chokepoint. Given its role in shaping the international system, the United States has a stake in every corner of the globe. The United States asserts that it was among the first states to recognize the independence of Central Asian states and has assisted these countries in establishing their sovereignty. Although the withdrawal of US troops from Afghanistan has caused some negative consequences for Central Asian countries, it does not mean that US interests in the region have ended. But the development of a new strategy by the United States for the Central Asian region is an important issue. Additionally, the United States must use its influence in Central Asia to counteract Russia's hegemony there and provide a barrier against China's massive inflows.